Pengembangan Media Animasi untuk Mendukung Pembelajaran Berbasis TPACK dengan POWTOON pada Materi Torsi SMA Kelas XI - Zakaria Al Farizi; Dwi Sulisworo; M H Hasan; M E Rusdin (Jurnal Penelitian Pembelajaran Fisika, 2019)
The purpose of this study is to develop learning animation media on TPACK-based torsion material. Media is created and developed using the Powtoon application. Media development needs to be done based on journal analysis carried out and found that students have difficulty being able to receive lessons in class and one of the reasons is the use of inappropriate learning media. In addition, with the advancement of technology, it is currently encouraging every educator to take part in it. The research method used was R & D (Reserch and Development) with two trial subjects namely material experts and media experts to test the feasibility of the media. From the results of validation, presentations for material experts were 72.6% and 96.4% media experts, and for percentages overall the animation media scored 82% or in the Likert scale in a very good category so the animation media to support TPACK based learning with Powtoon can be applied in learning in class.